Stress recovery behavior of an Fe-Mn-Si shape memory alloy. (15th September 2021) - Gu, Xiang-Lin; Chen, Zhen-Yu; Yu, Qian-Qian; Ghafoori, Elyas
Highlights: Effect of high activation temperatures on recovery stress of Fe-SMA was studied. A cost-effective activation strategy was put forward in terms of recovery stress. Evolution of recovery stress of activated Fe-SMA subjected to fatigue was assessed. Abstract: This study investigated the stress recovery behavior of an Fe-Mn-Si-Cr-Ni-VC shape memory alloy for prestressed strengthening, focusing on high-temperature activation of the alloy. The effects of different prestrain levels (1%, 2%, 4%, 6% and 8%), activation temperatures (100, 150, 200, 250, 300, 350, and 455 °C), and initial preloads (50, 100 and 150 MPa) on recovery stress were evaluated to propose an optimum activation strategy. In addition, mechanical properties of the Fe-SMA after activation, including the performance under a second high-temperature activation (up to 455 °C) and high-cycle fatigue (HCF) loadings (stress-controlled with a stress range of 57 MPa), were studied. According to the results, a prestrain level of 2% was found to be the optimum level when the activation temperature was below 200 °C. However, at higher activation temperatures, an increased prestrain resulted in an increase in the recovery stress. In this study, the specimens prestrained by 4 and 8% and activated by 350 °C led to a recovery stress of 421 and 445 MPa, respectively. According to the fatigue test results, the recovery stress decreased by 12 – 15% after two million load cycles, regardless of the activation temperature.